Pengembangan Sistem Informasi Paduan Suara Mahasiswa Universitas Diponegoro Berbasis Web dan SMS - Liga Filosa; R. Rizal Isnanto; Adian Fatchur Rochim (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
Today, technology has become ours primary need. The ease of getting or giving information by using technology make people do their jobs easily. Diponegoro University Choir (PSM) is one of choir that have good reputation in local, national and international. But PSM do not have any official website that can gives information to the people. Every years, the number of recruits is increasing, and the process of registeration is still done manually. Based on that problem, the organization needs an web-based Information System and SMS gateway to support information giving process and its own member data maintenance.The Information System is built using PHP Framework Codeignitier language program, javascript for the dynamic appearance, and MySQL for the database. The System’s development process uses waterfall method. This method is included with analysis of needs, analysis, design, implementation and testing. The model of system is built using object oriented UML (Unified Modeling Language) includes Use Case diagram, Class diagram and Sequence diagram